The mouse gene expression database: New features and how to use them effectively. Issue 8 (18th June 2015) - Finger, Jacqueline H.; Smith, Constance M.; Hayamizu, Terry F.; McCright, Ingeborg J.; Xu, Jingxia; Eppig, Janan T.; Kadin, James A.; Richardson, Joel E.; Ringwald, Martin; Vize, Peter; Westerfiled, Monte
Summary The Gene Expression Database (GXD) is an extensive and freely available community resource of mouse developmental expression data. GXD curates and integrates expression data from the literature, via electronic data submissions, and by collaborations with large‐scale projects. As an integral component of the Mouse Genome Informatics Resource, GXD combines expression data with genetic, functional, phenotypic, and disease‐related data, and provides tools for the research community to search for and analyze expression data in this larger context. Recent enhancements include: an interactive browser to navigate the mouse developmental anatomy and find expression data for specific anatomical structures; the capability to search for expression data of genes located in specific genomic regions, supporting the identification of disease candidate genes; a summary displaying all the expression images that meet specified search criteria; interactive matrix views that provide overviews of spatio‐temporal expression patterns (Tissue × Stage Matrix) and enable the comparison of expression patterns between genes (Tissue × Gene Matrix); data zoom and filter utilities to iteratively refine summary displays and data sets; and gene‐based links to expression data from other model organisms, such as chicken, Xenopus, and zebrafish, fostering comparative expression analysis for species that are highly relevant for developmental research. genesis 53:510–522, 2015. © 2015 Wiley Periodicals, Inc.